Integrated Molecular and Morphological Studies of the Daucus guttatus Complex (Apiaceae) - Arbizu, CI (2016)
We thank Kathleen Reitsma at the North Central Regional Plant Introduction Station in Ames, Iowa for providing germplasm. This paper represents partial fulfillment of a Ph.D. degree for CA in Plant Breeding and Plant Genetics at the University of Wisconsin–Madison. CA is partly funded by the National Council of Science and Technology of Perú (Concytec, by its initials in Spanish). We appreciate the comments of two anonymous reviewers and Editor-in Chief James Smith that greatly improved our manuscript.